SPIRITUAL TOURIST CENTRES IN THIRUVANNAMALAI DISTRICT (Journal of Pharmaceutical Negative Results, 2022)
The travel industry addresses a significant financial movement in numerous nations throughout the planet. It includes individuals, their manifestations, and the social, monetary, and social conditions that impact their lives. The regular and man-made climate of space comprises one of the essential elements of the vacationer items. The State lies at the southern tip of India, encircled by the States of Pondicherry, Kerala, Andhra Pradesh, and Karnataka. The locale has been the home of Tamil individuals since something like 500 BCE. Its authority language Tamil has been being used in engravings and writing for more than 2000 years the ten-day "Karthigai Deepam Festival" (light lit at the highest point of the sacrosanct slope) draws in lakhs of individuals from adjoining states. Devikkapuram is arranged 50 Km from Thiruvannamalai. Spots of interest in the Javvadhu slopes are Beema falls, Komutteri Lake, Kavanur observatory, Amirithi woodland, and the glasshouse.